The impact of green exercise on test of performance strategies, physical variables and counter-time performance for Egyptian epee fencers - Abdel-Rahman, O.; Magdy, S. (Science, Movement & Health, 2014)
Purpose. Green exercise refers to physical exercise undertaken in natural environments. this study aimed to investigated the impact of green exercise on Test of Performance Strategies (TOPS), physical variables and countertime performance for Egyptian epee fencers Methods. Twenty professional Epee fencers (mean +/- SD age, 21.2 +/- 2.05 years. High, 179.64 +/- 7.31 cm. Weight, 77.22 +/- 6.77 kg). Training experience 10.12 +/- 2.11 years), all participations divided into equally to (2) groups (experimental groups -10 Epee fencers) and (control group -10 Epee fencers) from the Egyptian fencing clubs, the experimental group performed the green exercises (outdoor) which contain (warm up, stretch, and body weight exercises) for (8) weeks, and the control group practiced the traditional training only into the hall (indoor). Only the part of warm up is the different between the two groups .The data collected from counter-time performance test by using off camera 100 frames / second). And physical abilities tests (flexibility, agility) before and after the programs for the two groups. Results. Significant changes between posttests scores for the control and experimental groups (P. 0.05) in physical tests and counter time performance, (TOPS) variables in training Goal setting, Activation, Attentional control for experimental group, and (TOPS) in competition Goal setting, Activation, Negative thinking. However no significant differences were shown between other variables (P. 0.05). Conclusions. Under the condition of our study, green exercise intervention for eight weeks has a beneficial effect on Test of Performance Strategies (TOPS), physical variables and counter-time performance for Egyptian epee fencers.